2004
DOI: 10.1136/thx.2004.022475
|View full text |Cite
|
Sign up to set email alerts
|

Use of inhaled corticosteroids following discharge from an emergency department for an acute exacerbation of asthma

Abstract: Background: Most patients who have an asthma exacerbation leading to a visit to an emergency department (ED) will benefit from treatment with inhaled corticosteroids (ICS) at discharge. We investigated whether asthmatic children and adolescents were receiving ICS after discharge from the ED and identified the characteristics of patients and physicians associated with their use. Methods: A cohort of 4042 asthmatic patients aged 5-17 years was selected from the administrative database of the Régie de l'assurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…The RAMQ and MED-ECHO databases have often been used in the past for epidemiologic research in the field of asthma. [19][20][21][22][23] Data recorded in the RAMQ Medication Prescriptions database and the medical diagnosis for asthma recorded in the RAMQ Medical Services database have been formally evaluated and found to be valid. 24,25 Moreover, some medical diagnoses recorded in the MED-ECHO database have been found to be valid.…”
Section: Source Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The RAMQ and MED-ECHO databases have often been used in the past for epidemiologic research in the field of asthma. [19][20][21][22][23] Data recorded in the RAMQ Medication Prescriptions database and the medical diagnosis for asthma recorded in the RAMQ Medical Services database have been formally evaluated and found to be valid. 24,25 Moreover, some medical diagnoses recorded in the MED-ECHO database have been found to be valid.…”
Section: Source Of Datamentioning
confidence: 99%
“…The mother's sociodemographic characteristics included age at conception (18,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and 35 years), receipt of social assistance during pregnancy or 2 years prior (yes/no), area of residence at delivery (rural/urban), and level of education (12, 13 years, and missing). Maternal chronic conditions included diabetes mellitus (yes/no), epilepsy (yes/no), and use of recognized teratogenic medications during the first trimester of pregnancy (yes/no).…”
Section: Confounding Variablesmentioning
confidence: 99%
“…The RAMQ Medical Services file includes claims data on medical services such as site of medical practice (outpatient clinic, emergency department [ED], hospitalization); nature of the medical act, date, and diagnostic information (International Classification of Disease, 9th revision [ICD-9] codes); and the encrypted identification and physician's specialty. 26 The RAMQ Prescription Drugs file, which has been validated for research and previously used for pharmacoepidemiologic research studies, 27,28 contains data on prescriptions filled at community pharmacies: drug name, date, dose, quantity, and duration as indicated by the pharmacist, as well as the encrypted identification and prescribing physician's specialty. The MED-ECHO database contains data on acute care hospitalizations, such as date of admission, length of stay, and primary and secondary diagnoses.…”
Section: Sources Of Datamentioning
confidence: 99%
“…Factors such as personal experience of a severe asthma attack and changes in asthma management after an admission can cause patients in the post-discharge period to have different adherence, and respond differently, to controller therapies. Blais et al investigated the long-term adherence to inhaler controllers in children and adolescents after an asthma exacerbation [32]. They reported that a prescription for SCS was a significant predictor of long-term use of ICS.…”
Section: Discussionmentioning
confidence: 99%